A transformation of racist discourse? Colour-blind racism and biological racism in Dutch secondary schooling (1968–2017). - Sijpenhof, Maria Luce (Paedagogica Historica, 2020)
Scholars have observed a re-emergence of biological racism in the Netherlands. I question whether this form of racism is also making a comeback in Dutch secondary schooling, by drawing on critical race theory and Bonilla-Silva's frames of colour-blind racism. Data for this study were gathered through an analysis of 200 history textbooks (1968-2017), 28 interviews of (former) Dutch (mostly "white") teachers and 35 interviews of former (mostly "Black") students. The study finds that textbooks employ colour-blind racist frames (and in some cases racially essentialist and anti-racist discourses) regarding black history. Likewise, white (former) teachers consistently use colour-blind discourses and to lesser extent utilise racially essentialist and anti-racist discourses to make sense of race. This study demonstrates that Dutch teachers use very similar frames to what (researchers have found) people utilise in the US. Also, Black former students are much more likely to narrate anti-racist discourses, but showcase colour-blind discourses and (sometimes) racially essentialist discourses, as well. Thus, colour-blind ideologies influence even those who are negatively affected by it. Although the expressions of racism shift over time, this study illustrates that we cannot affirm a re-emergence of biological racism, as colour-blind discourses remain equally intact in the 50 years studied.